Environmental Influence on the Measurement Results when Verifying and Calibrating Radar Level Gauges - Markovič, Jaromír; Schreier, Zbyněk; Ďuriš, Stanislav; Krivosudská, Jana (Manufacturing Technology Journal, 2016)
The present paper deals with the metrology, especially with the legal metrology that is responsible for assuring the uniformity and correctness of measurements. In addition to the definition and explanation of the basic terms and principles applied in the metrology, the paper presents especially the results of the scientific and research work in the cross-disciplinary fields of the legal metrology in Slovakia, namely in design and realization of a new measuring system for the verification of the radar level gauges.
Keywords: automatic level gauge; radar level gauge; verification; calibration; electromagnetic waves